Optimalisasi Manajemen Sumber Daya pada Mahasiswa Magang MBKM - Siti Ikramatoun; Cut Lusi Chairunnisak; Nurul Fajri; Ibnu Phonna Nurdin; Vini Aora; Fathiya Rahma (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Skills and abilities are needed by students in carrying out MBKM internship activities in various institutions. This is necessary so that students can perform at their best during their internships at various institutions. In addition to the need for internships, the skills acquired by students can be implemented in the workforce once they graduate from their bachelor's degree. This service aims to realize the golden generation in 2045 and the fourth astacita, which is to strengthen human resource development. There are 3 main activities provided during this training, namely: three service activities that include strengthening work ethics, cultural and work ethos training, and enhancing digitalization skills. These three main activities are the core activities that must be attended by intern students as an initial step to optimize their skills and abilities. Based on the results obtained, such optimization programs are very helpful for students as an initial step in preparing for internships at institutions. In addition, students have knowledge of how to quickly adapt in their institutions. This is very relevant and needs to be continuously developed to ensure that students are optimally prepared to face an increasingly competitive in world of work.